FEAR RHETORIC IN THE ONLINE NEWS DISCOURSE ON THE COVID-19 PANDEMIC IN TEUN VAN DIJK’S CRITICAL DISCOURSE ANALYSIS - Dery Rovino; Fadhilah Nur Afifah; Tiara Aqwya Aningrum Kusuma Wardani (Journal of English Language and Culture, 2021)
The news media, once thought to be only as a tool of information delivery, has subtly shifted its roles as an agent of (de)constructing thoughts, introducing, or denoting fear especially in appalling news. This raises a question whether the news on the COVID-19 pandemic is only for transmitting news updates on the pandemic condition or agenda-driven. However, research tapping into the imbued messages in language complexity in this context seems minimal. This study aims to uncover the language elements that sign fear in a news text. This research focuses on how fear is imbued in three online English-language newspaper articles in Indonesia published by the Jakarta Post, thereby the rhetoric of fear. The three articles discussed the spread of COVID-19 in Indonesia.  In this study, CDA is devised to reveal the traces of fear-embedded language choices found in the three online newspaper articles. Researchers used the critical analysis discourse model of Teun A. Van Dijk (1993) and the three elements of discourse (1993): micro, macro, and superstructure. Findings indicated that there were common uses of euphemism, dysphemism, and orthophemism to refine the language being conveyed. This study classified euphemism into five objectives: (1) evasive maneuver to prevent mass panic; (2) speech refinement to soften offence, insults, and/ or other language expressions that may result to humiliation; (3) diplomacy tool; (4) language replacement for taboo or vulgar language choices or those endowed with negative connotation (5) tool for satire, sarcasm and subtle criticism. This study also revealed some linguistic decisions, such as lexicon choices and strategies on sentence construction, subtly evident not only to impose fear, but at the same time to dispose it. Researchers hope that this study may assist the readers in pinpointing subtleties in author’s tone and tendency.